The effect of photomath applications on mathematical problem solving: systematic literature review - Putri, Sri Yayuk Juana; Cahyanti, Cahyanti (Polyhedron International Journal in Mathematics Education, 2024)
The purpose of this research was to analyze the impact of the Photomath application on students' mathematical problem-solving abilities. This study employed a systematic literature review method using the PRISMA approach, where relevant articles were There were 5 articles that were further analyzed. collected and analyzed following the PRISMA flowchart. The results revealed various research methodologies used in studies involving Photomath, publication trends in recent years, and evidence of its influence on enhancing students' problem-solving skills. Based on these findings, it was recommended that teachers integrate the Photomath application as a supplementary tool in mathematics learning to help students understand and solve complex mathematical problems effectively.